(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The purpose of this paper is to determine which variables influence consumers’ intentions towards purchasing natural cosmetics. Several variables are included in the regression analysis such as age, gender, consumers’ purchase tendency towards organic food, consumers’ new natural cosmetics brands and consumers’ tendency towards health consciousness. The data was collected through an online survey questionnaire using the purposive sample of 204 consumers from the Dubrovnik-Neretva County in March and April of 2015. Various statistical analyses were used such as binary logistic regression and correlation analysis. Binary logistic regression results show that gender, consumers’ purchase tendency towards organic food and consumers’ purchase tendency towards new natural cosmetics brands have an influence on consumer purchase intentions. However, consumers’ tendency towards health consciousness has no influence on consumers’ intentions towards purchasing natural cosmetics. Results of the correlation analysis indicate that there is a strong positive correlation between purchase intentions towards natural cosmetics and consumer references of natural cosmetics. The findings may be useful to online retailers, as well as marketers and practitioners to recognize and better understand the new trends that occur in the industry of natural cosmetics. Keywords: Consumer purchase intentions, consumer tendencies, natural cosmetics